Are we missing something when evaluating adsorbents for CO2 capture at the system level?. Issue 12 (7th October 2021) - Balogun, Hammed A.; Bahamon, Daniel; AlMenhali, Saeed; Vega, Lourdes F.; Alhajaj, Ahmed
Abstract : The right ingredients and scales for a proper assessment of adsorbents for CO2 capture. Abstract : Adsorption of CO2 with porous solid materials is gaining attention as a promising CO2 capture technology due to the potential improvement in energy efficiency and cost reductions. This study investigates for the first time the potential performance of the MOFs Cu-BTC, Mg-MOF-74, and UTSA-16 for CO2 capture at a commercial large-scale using multiscale modeling; in addition, a selected activated carbon was included for comparative purposes, and zeolite 13X was used as the benchmark. We have developed a multiscale model that integrates molecular simulation results with a process model of a pressure/vacuum swing adsorption (P/VSA) process. The model was first validated at the pilot scale and then used to assess the performance of the above-mentioned adsorbents and processes attached to a 550 MW coal plant, in order to achieve the 90% recovery and 95% purity targets of the US Department of Energy. The optimal design, scheduling and operating conditions of these adsorbents were obtained while minimizing total cost and improving the non-monetized key performance indicators (KPIs) such as productivity, selectivity, working capacity, energy consumption and the modified adsorption figure of merit (AFM) obtained in global sensitivity analyses. A key finding from this study is that the recently proposed UTSA-16 MOF can be as good as the traditional zeolite 13X for industrial-scale post-combustion capture and compression, at a cost of <45 t CO2 −1 and an energy consumption of <550 kW h e t CO2 −1 . It is also shown that, sometimes, using specific KPIs for the evaluation of adsorbents can lead to misleading results as the overall performance depends on the dynamics of the operating conditions at the cyclic steady state, the material cost, the scheduling and the column geometry. This study underlines the importance of utilizing a detailed multiscale model and system-level analysis for the reliable assessment of different adsorbents for industrial-scale carbon capture.